UI / UX Design Automation Services Library and Archives of East Java by Using Webuse Heuristic Method - Firmansyah, Helmi Previanto; , S.Si., MM., Sulistiowati; Kartikasari, M.Si., Puspita (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
The East Java Library and Archives Automation application began operations in 2010 developed by the library automation section and financed by the Government of East Java. One of the library automation applications is library library search application available in three computer units. Collection search apps can browse library collections quickly, but after interviews with 30 library visitors who used the collection search application there are still some problems with the collection search app view. The results of these interviews indicate there are still some look of collection search applications that need to be improved. In order to fix display problems in the library library search application, UI / UX design will be done using WEBUSE Heuristic method. The WEBUSE Heuristic Method can find errors and measure the success of an interface design. The results obtained through the WEBUSE Heuristic method will serve as the basis for designing UI / UX recommendations to improve the look and quality of libraries library search applications. UI / UX design using WEBUSE Heuristic method resulted in 12 interface design designs as a recommendation to improve the interface design of library collection search application.